ANALISIS KEBIJAKAN PEMERINTAH DAERAH DALAM PENCEGAHAN CORONAVIRUS DISEASE (COVID-19) DENGAN PENDEKATAN KOMUNIKASI, MEDIA DAN BUDAYA - M Mansyur; Tina Kartika (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
This research uses content analysis method. This method discusses in depth the contents of written or printed information in mass media. Based on research and analysis conducted, I found that the Coronavirus Disease (Covid-19) prevention policy by the Four Regional Provinces was appropriate and contained a perspective of communication and cultural media in it.